2015
DOI: 10.17860/efd.42583
|View full text |Cite
|
Sign up to set email alerts
|

Eğitim Sisteminin Eleştirel Pedagoji Perspektifinden Bir Değerlendirmesi

Abstract: Öz: Bu araştırmanın amacı mevcut eğitim sistemini eleştirel pedagoji perspektifinden öğretmen görüşlerine göre ele almak ve tartışmaya açmaktır. Nitel bir araştırma olan ve tarama modelinde tasarımlanan bu çalışma, veri toplama tekniklerinden, bireysel görüşme yöntemi kullanılarak gerçekleştirilmiştir. Veri toplama aracı olarak, yarı yapılandırılmış görüşme formu kullanılmıştır. Çalışma grubuna maksimum çeşitlilik örnekleme yöntemi kullanılarak seçilen Eğitim Bir Sen üyesi 4, Eğitim Sen üyesi 3, Türk Eğitim Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
Order By: Relevance
“…The participants who evaluated the education system as poor quality pointed out that the education system is mostly structured on maintaining the existing structure and that there is no democracy and freedom. The present result coincides with the study by Kesik and Bayram (2015). In this study, it was concluded that the education system protects and maintains the existing social structure instead of realizing a transformation; the over-centralized and status quo nature of the education system, the lack of opportunities for change, and the fact that teachers, although they have a vital role, stand behind this transformation create obstacles to transformation.…”
Section: Resultssupporting
confidence: 90%
“…The participants who evaluated the education system as poor quality pointed out that the education system is mostly structured on maintaining the existing structure and that there is no democracy and freedom. The present result coincides with the study by Kesik and Bayram (2015). In this study, it was concluded that the education system protects and maintains the existing social structure instead of realizing a transformation; the over-centralized and status quo nature of the education system, the lack of opportunities for change, and the fact that teachers, although they have a vital role, stand behind this transformation create obstacles to transformation.…”
Section: Resultssupporting
confidence: 90%
“…In some studies, it was concluded that the students who have higher critical thinking disposition have also better academic achievements (Akbıyık, 2002;Akbıyık and Seferoğlu, 2006;Çam, 2006;Kurnaz, 2007;Ünal, 2006). However, it was concluded that critical thinking dispositions of students are low in many studies (Akar and Kara, 2016;Bayram and Kesik, 2015;Çalışkan, 2009;Ersoy and Başer, 2011;Kaloç, 2005;Örge-Yaşar, 2014).…”
Section: Introductionmentioning
confidence: 99%